Pervan Beg Mecmu’Atü’n-Neza’ir: (580b-603a) - Öztürkçü , İbrahim (My University, 2004)
Çalışmamızın konusunu , Topkapı Sarayı Kütüphanes'inde 406 numaraya kayıtlı olan Pervane Bey'in tertip ettiği nazire mecmuasının 580b-603a varakları arasındaki gazeller ve bunlara yazılan nazireler teşkil etmektedir. Söz konusu varaklar arasındaki bütün şiirler , çalışmamızda transkripsiyonlu metin haline getirilmiştir. Ayrıca , divanları yeni yayınlanmış bulunan şairlerden , divanlarına ulaşabildiğimiz kısımlarıyla metnimizdeki gazeller karşılaştırılmış ve aralarındaki nüsha farkları dipnotta belirtilmiştir. Bu çalışmanın sonucunda , metnimizde 291 şiir yer almıştır. Yine çalışmamızda , metne ait bir dizin düzenlenmiştir. Metnimizdeki gazellerin diziliş sırasını gösteren nazireler listesi de eklenmiştir. In the library of Topkapı Palace , there are quite many Works which were published in Ottoman time. Our research work is registered to the number 406 in Topkapı Palace. This work is called as Pervane Bey Nazire Periodical. It consists of poems which were gathered tugether. In other words these poems , which are included in the periodical , are defined as nazire. Firstly we started to constitude the transcriptions of this poems. We compared the poems of the poets who were mentioned in our work with other poems of the same poets which were published in other works. We clarified the differences between these works in footnote. Consequently In our work , there are 291 poems which were written by 115 poets. On the other hand we arranged an index at the end of text. Moreover we added a list of poems which shows the order of arrangement of them. We hopefully think that our work seems to be the complementary of the other works which have been studied on the same subject so far.
Keywords: Edebiyat; Osmanlıca edebiyat; Osmanlıca şiir (Divan şiiri); Türk Edebiyatı